1986
DOI: 10.1021/bi00354a015
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and inhibitor studies of thermolysin-like neutral metalloendopeptidase from kidney membrane fractions. Comparison with bacterial thermolysin

Abstract: The inhibitory constants of a series of synthetic N-carboxymethyl peptide inhibitors and the kinetic parameters (Km, kcat, and kcat/Km) of a series of model synthetic substrates were determined for the membrane-bound kidney metalloendopeptidase isolated from rabbit kidney and compared with those of bacterial thermolysin. The two enzymes show striking similarities with respect to structural requirements for substrate binding to the hydrophobic pocket at the S1' subsite of the active site. Both enzymes showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…These substrates are hydrolyzed at the Ala-Phe and Ala-Leu bonds, respectively, conforming with the primary specificity of the enzyme, known to cleave internal peptide bonds of peptides on the amino side of hydrophobic amino acid residues [1,6,13]. The hydrophobic Phe or Leu residues of the substrates interact with the primary specificity site of the enzyme S'~, whereas the two Ala residues interact with the secondary sub-sites St and S 2 (according to the nomenclature of Schechter and Berger; [21]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These substrates are hydrolyzed at the Ala-Phe and Ala-Leu bonds, respectively, conforming with the primary specificity of the enzyme, known to cleave internal peptide bonds of peptides on the amino side of hydrophobic amino acid residues [1,6,13]. The hydrophobic Phe or Leu residues of the substrates interact with the primary specificity site of the enzyme S'~, whereas the two Ala residues interact with the secondary sub-sites St and S 2 (according to the nomenclature of Schechter and Berger; [21]).…”
Section: Resultsmentioning
confidence: 99%
“…Neutral endopeptidase (EC 3.4.24.11) or neprilysin (NEP), an ectoenzyme present on the surface of many cell types [1][2][3], is a zinc metalloendopeptidase with a broad specificity. It hydrolyzes internal peptide bonds of peptides on the amino side of hydrophobic amino acid residues and in this respect it resembles the well-characterized bacterial zinc metalloproteinase thermolysin (EC 3.4.24.27) [4][5][6]. NEP has been implicated in the metabolism and regulation of a variety of biologically active peptides, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the initial reaction rates at varying substrate concentrations (Figure 3b) yielded the characteristic proteolytic constants (kcat/KM) for the different peptide sequences (inset of Figure 3b and Table 1). 61 Note that our tandem assays allow kinetic measurements for unlabeled peptides, while previous assays were carried out with peptides carrying fluorescent labels such as 2-naphthylamide (2NA) 62 or dansyl. 63 The structural differences prevent a direct comparison of the absolute proteolytic constants.…”
Section: Resultsmentioning
confidence: 99%
“…The observed specificity of BoNT/B, however, clearly places these toxins into a distinct class of proteases. Previous studies on the substrate specificity of several neutral proteinases using model peptide substrates have shown that the rate of proteolysis is most influenced by the nature of the amino acid residues at the site of cleavage with residues at positions P,, P,, P',, P; (Schechter and Berger, 1967) having most influence on the reaction rate (Bouvier et al, 1990;Makinen et al, 1989;Morihara and Tsuzuki, 1970;Pozsgay et al, 1986). For all neutral proteases studied it has been possible to define short (< 10 amino acids) peptide substrates which are efficiently cleaved by the enzyme.…”
Section: Discussionmentioning
confidence: 99%